Age-Related Features of Depression in Residence of the Arctic Zone - A.V. Klimak; O.A. Kharkova; A.V. Kudryavtsev (Клиническая и специальная психология)
The study aims to investigate the age-related characteristics of depression among residents of the Arctic zone, considering gender and the period of data collection. This cross-sectional study utilized data collected as part of the Cardiovascular Disease Project (N=2380). Study participants were randomly selected using stratified sampling based on age and gender. Depression was assessed using the PHQ-9 depression scale, which consists of 9 questions based on the DSM-IV diagnostic criteria for depression, asking about the patient's experiences over the past 2 weeks. In the course of studying the age-related characteristics of depression among residents of the Arctic zone, it was found that certain symptoms of depression are more prevalent in young people; however, the chance of moderate to severe depression is significantly higher in older women.